Interlanguage or technology? Capitalization in a learner corpus of english as a foreign language - Torrado, Milagros; Font, Carmen (Opción, 2016)
This article analyses a specific corpus from students of English for the Degree of Early years Education at UNIR University, Spain. It collects the input of more than one hundred students in the subject “ICT tools applied to the learning of English language”. The corpus is being analyzed by a group of researchers from the English Department at UNIR, so as to offer a taxonomy of errors and mistakes in the frame of undergraduate degrees. The results examine the use of capital letters in the data collected. The inputs have been sorted out with a specific corpus management program.